Innovative approaches to standardisation in forest commodity science: Trends and prospects - O. Sytnyk; I. Kimeichuk (Наукові доповіді Національного університету біоресурсів і природокористування України)
It is important to create a regulatory environment for the integration of digital technologies into standardisation procedures. The aim of the study was to examine the possibilities for harmonising the Ukrainian regulatory framework with international requirements, identify barriers to the introduction of innovations, and outline the prospects for the development of the industry until 2030. The study used methods of comparative analysis of regulatory documents, content analysis of publications, analytical and descriptive methods. Both Ukrainian (DSTU) and international standards (ISO, FSC, PEFC) regulating the requirements for the quality, safety and environmental friendliness of forest products were considered. The study revealed modern innovative approaches to standardisation in forest commodity science, among which digital technologies, blockchain systems, artificial intelligence algorithms and remote monitoring tools played a key role. Based on the analysis of foreign experience (Germany, Canada, Sweden) and Ukrainian practice, the effectiveness of digital platforms for compliance control, online certification systems, the use of drones and satellite monitoring has been proven. It has been determined that leading countries have already implemented integrated ecosystems that combine standards, intelligent algorithms, and certification chains. In Ukraine, electronic product coding and the creation of databases of certified sites have been initiated, but further development is hampered by underfunding, fragmented policies and a lack of personnel. Areas for improvement have been proposed: attracting international technical assistance, developing public-private partnerships and updating educational programmes. Particular attention is paid to the need to form a single unified system for the evaluation of forest products in accordance with international trade requirements. The results of this study can serve as a basis for strategic decisions in the field of modernisation of the Ukrainian standardisation system